Thermographic analysis of the effect of composite type, layering method, and curing light on the temperature rise of photo-cured composites in tooth cavities. Issue 10 (October 2017) - Kim, Min-Jung; Kim, Ryan Jin-Young; Ferracane, Jack; Lee, In-Bog
Abstract: Objectives: The purpose of this study was to investigate temperature rise in the composite and dentin of a class I cavity in extracted human molars under different restoration conditions, including the use of different composite types, layering methods, and curing lights. Methods: Open occlusal cavities were prepared on 28 extracted human molars. A conventional (Filtek Z250) and a bulk-fill (Filtek Bulk Fill Posterior; BFP) composite were used to restore the preparations. BFP was incrementally layered or bulk-filled. Bulk-filled BFP was cured with two different lights, the Elipar S10 and the BeLite. Each layer was illuminated for 20 s, while thermograms of the specimens were recorded for 100 s using an infrared thermal camera. Temperature changes on the composite and dentin surfaces were obtained at points of interest (POI) pertaining to successive incremental distances of 0.75 mm from the top of the cavity to the pulp. The polymerization kinetics of each composite was determined using photo-differential scanning calorimetry. Results: The greatest temperature rise was observed 0.75 mm apical from the top of the cavity. All groups showed over 6 °C maximum temperature rise (ΔTmax ) at the pulpal side of the dentin. Upon curing, Z250 reached ΔT = 5 °C faster than BFP; however, ΔTmax of the two composites were comparable at any POI. Bulk filling showed greater ΔTmax than incremental filling at 0.75 mm apical from the top and in the middle of the cavity. The Elipar S10 light generated faster temperature changes in the curing composite at all recorded positions throughout the depth of the cavity and greater ΔTmax in all POIs compared to BeLite. Significance: Real-time thermographic analysis demonstrated that the composite type and layering method did not influence the temperature rise at the pulpal side of dentin during composite restoration of an occlusal preparation in a tooth. The amount and initial rate of temperature increase was most affected by the radiant exposure of the light curing unit. Within the limitations of this in vitro study, when irradiation time is constant, a curing light with higher radiant power can induce relatively high thermal transfer, thereby increasing the risk of pulpal damage.